TEACHER’S CODE SWITCHING IN ENGLISH CLASSROOM AT SMAN 2 BUKITTINGGI, WEST SUMATRA - Sari, Mike Nurmalia (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
This research aimed to see the code-switching did by the English teacher at SMAN 2 Bukittinggi, West Sumatra and the purposes of doing so. The population of the research was all English teachers at the school, and the sample is one English teacher in the school, picked randomly and the teacher was non-native speaker of English. Technique of data collection was audio recording that was gathered by taking several audio recordings. Method of data analysis was done through analyzing the transcript of teaching and learning process in English subject. All the activities during 100 minutes teaching and learning were analyzed further. The result of the research showed that mostly during the lesson, the teacher used the target language, in amount of 69.54% from the total talk teacher did during the lesson. Therefore, it shows that the tendency that teacher had in her mind she should use as much English as possible in the classroom. For the function of doing code-switching, mostly because the teacher wanted to clarify the information (49.1%) and classroom management (25%). Key Words: Code-Switching, English Subject, Classroom Communication